miR-181b-5p May Regulate Muscle Growth in Tilapia by Targeting Myostatin b - Zhao, Zaoya; Yu, Xiaozheng; Jia, Jirong; Yang, Guokun; Sun, Caiyun; Li, Wensheng (Frontiers in Endocrinology, 2019)
Background: Myostatin (Mstn), a member of TGF-β superfamily, is a negative regulator of skeletal muscle mass in mammals. Precise regulation of Mstn expression is important for the somite growth in fish. MicroRNA (miRNA), a type of small non-coding RNA, regulates gene expression at the post-transcriptional level and participates in various physiological functions. Growing evidences have emphasized the importance of miRNA in the development of skeletal muscle. Aims: This study aims to study how miRNAs regulate myostatin b (Mstnb) post-transcriptionally in tilapia. Methods/Results: Mstnb 3’ UTR sequences were obtained and the results of tissue distribution showed that Mstnb was expressed in several tissues, including brain, white muscle, gut and adipose tissue. A total of 1992 miRNAs were predicted to target Mstnb in tilapia using bioinformatics, and a dual-luciferase reporter experiment confirmed that miR-181a/b-5p, miR-30-3p, miR-200a and miR-27a were the target miRNAs of Mstnb. Mutagenesis of the miR-181b-5p binding sites of Mstnb significantly increased the luciferase signal compared to the wild-type Mstnb. In tilapia primary muscle cells, overexpression of miR-181b-5p led to the down-regulation of Mstnb expression, and the inhibitory effect of Mstnb on the downstream genes was dismissed, while inhibition of miR-181b-5p could reverse these phenomena. Conclusion: Taken together, our results suggested that miR-181b-5p could promote the growth of skeletal muscle by decreasing the Mstnb protein level in tilapia.